Influencing the critically ill patient? A qualitative study with teams in German intensive care - Seidlein, Anna-Henrikje; Jöbges, Susanne (Frontiers in Anesthesiology, 2025)
IntroductionNurses and physicians can influence the patient's will in various ways during intensive care treatment, whereby certain strategies fall into the realm of formal and informal coercion. Understanding and addressing these dynamics is crucial for humanized intensive care which promotes patient autonomy, minimizes coercion and fosters positive support strategies. We aimed to investigate which possibilities and forms of (un)intentional influencing and overriding of the patient's will between “formal” (physical restraint, sedation) and “informal” (psychological measures such as deception and threats) coercion are used in the intensive care unit (ICU).MethodIn this qualitative study, semi-structured interviews were conducted with 30 nurses and physicians working in different German ICUs between September 2022 and February 2023. Participants were selected using a purposive sampling technique to support the heterogeneity of the sample. Interviews were analysed using thematic analysis.ResultsFive different forms of influence aiming at motivation, convincement (argumentative or manipulative), subordination and control were identified, along with different communicative practices (e.g., information, deception, lie, persuasion, threat) and other strategies (e.g., physical restraint) to reach the corresponding goal. The different forms are used simultaneously or alternately, i.e., they cannot be categorized in terms of an escalation hierarchy. The boundaries between support, informal and formal coercion are blurred, sometimes subtly.DiscussionIn the ICU nurses and physicians influence the patient's will using many strategies; some despite moral and legal concerns. Further research is needed to determine the frequency of informal coercion in larger samples and different intercultural contexts.